20+11c=7+12c+6

Simple and best practice solution for 20+11c=7+12c+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 20+11c=7+12c+6 equation:



20+11c=7+12c+6
We move all terms to the left:
20+11c-(7+12c+6)=0
We add all the numbers together, and all the variables
11c-(12c+13)+20=0
We get rid of parentheses
11c-12c-13+20=0
We add all the numbers together, and all the variables
-1c+7=0
We move all terms containing c to the left, all other terms to the right
-c=-7
c=-7/-1
c=+7

See similar equations:

| 7+18n=19n | | -8(6k-3)=k | | 7x+4(18-x)=96 | | 0.71-5.5p=-5.6p | | -5n=-71/2 | | 4z-18-9z=4-7z | | 8/11x88=64 | | -q-20=14+q | | 5(-2x+3)=55 | | 11x+180-6x=225 | | -8(5x-2)=336 | | -8.3=d+4.7= | | 10.9h=12.45+12.4h | | 4(3x-2)-4=4(x-4)+44 | | 4a-19=19+6a | | 1/9r=-4/45 | | 1/9r=-4/4 | | 10w=8w-14 | | f/4-25=-28 | | -2t+18=-2t-16+2t | | g/3+14=22 | | -4/3(x-6)=-24 | | 2(1/3x-6)=4 | | 5x-1(x+3)=1/3(9x+18)-5 | | -10.6r+13.63+16.76=-13.2r-19.27 | | 8x+6=7x-8=5x+2 | | (a+3)^2=25 | | a–12+2a=27 | | x^2-29=6x-18+5x-35 | | -10.6r+13.63+16.76=13.2r-29.27 | | -7/8k=-2 | | (2t+2)+4=3 |

Equations solver categories